Pengaruh Quality of Work Life Terhadap Kinerja Karyawan Melalui Deep Acting Sebagai Variabel Intervening pada Badan Pengelola Keuangan Pendapatan Daerah DI Kota Mamuju - Bahali, Hasnidar; Gani, Nuraeni; wahyudiyud (Study of Scientific and Behavioral Management, 2022)
ABSTRACT This study aims to determine the effect of quality of work life on deep acting, the effect of quality of work life on employee performance, the effect of deep acting on employee performance, and the effect of quality of work life through deep acting as an intervening variable on the performance of employees who work at Agency Offices. Regional Finance and Revenue Management in Mamuju City. The sample collection technique used is the saturated sample technique. The number of samples used was 116 respondents. The data processing method used in this study uses SPSS software. The results showed that quality of work life has a positive and significant effect on deep acting, quality of work life has a positive and significant effect on employee performance, deep acting has a positive and significant effect on employee performance, and quality of work life has a positive and significant effect through deep acting. Keywords: quality of work life, employee performance, deep acting